Composição química, avaliação antidepressiva e antioxidante do óleo essencial de Citrus sinensis (laranja doce) - Silva, Kímberly Stefanny da (2021)
Medicinal plants are a great source of medicines, being used by the population, and their biological activities are attributed to a great diversity of secondary metabolites. The species Citrus sinensis (Rutaceae) is known as “sweet orange”, it has been traditionally used to treat various disorders, including mental disorders. Depression is a chronic, multifactorial psychiatric disorder characterized by symptoms such as low mood and/or anhedonia, which may be accompanied by cognitive, neurovegetative deficits. Approximately 85% of patients with depression also have significant anxiety symptoms. The essential oil of C. sinensis has biological activities, such as antimicrobials, antioxidants, and is widely studied for having anxiolytic activity. Based on this, the work aimed to carry out the chemical characterization of the constituents present in the essential oil of C. sinensis, obtained from three (3) different suppliers, and to evaluate the antidepressant and antioxidant effect of the essential oil. Chemical characterization was performed using GC-MS, where five components were identified in the essential oil sample, with limonene being the major compound. For pharmacological tests, a dexamethasone-type behavior induction protocol was used. The project was approved by the Ethics Committee on the use of animals (CEUA/UFPB) of the Federal University of Paraíba, with approval certificate nº 8690120320. The Swiss mice were divided into six groups of 6 to 8 animals and submitted to behavioral tests as forced swimming, tail suspension and open field and after that, in vivo antioxidant tests were performed. In the forced swim test there was no difference between the groups treated with essential oil at doses 25, 50 and 100 mg/kg and the control group. In the tail suspension test, it was observed that CS 75 and CS 100 increased the immobility time when compared to the group treated with imipramine and there was no significant difference in the immobility time between the EO concentrations and the control. In the open field test the groups treated with CS 75 and CS 100 doses of essential oil also reduced the number of crossings when compared to the control group. The dexamethasone groups, CS 50, CS 75 and CS 100, increased the number of rearing when compared to the imipramine group. In the grooming parameter, there was a significant reduction in the frequency of self-cleaning between the dexamethasone, imipramine, CS 75 and CS 100 groups compared to the control group. The results found suggest that the groups treated with the EO of C. sinensis did not show an antidepressant effect when submitted to behavioral tests. In the in vivo antioxidant test, the essential oil showed an antioxidant effect in the glutathione reductase (GSH) test, as it significantly increased the GSH concentration in the CS 75 treated group when compared to the control and imipramine group. In the nitrite concentration, a significant increase was observed in the concentration of nitrite in the group treated with imipramine and CS 50, compared to the control group, suggesting that this increase leads to oxidation of cellular lipids, formation of free radicals and generation of reactive species of oxygen (ROS).